2020
DOI: 10.1158/0008-5472.can-20-1357
|View full text |Cite
|
Sign up to set email alerts
|

FAM46C and FNDC3A Are Multiple Myeloma Tumor Suppressors That Act in Concert to Impair Clearing of Protein Aggregates and Autophagy

Abstract: Multiple myeloma is a plasma cell neoplasm characterized by the production of unfolded immunoglobulins, which cause endoplasmic reticulum (ER) stress and sensitivity to proteasome inhibition. The genomic landscape of multiple myeloma is characterized by the loss of several genes rarely mutated in other cancers that may underline specific weaknesses of multiple myeloma cells. One of these is FAM46C that is lost in more than 10% of patients with multiple myeloma. We show here that FAM46C is part of a new complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 50 publications
7
60
0
Order By: Relevance
“…Accordingly, both TENT5A and TENT5C are clearly associated with membranes (Figure S6B; Bilska et al, 2020). TENT5C association with the ER was also recently confirmed by others, and the mechanism of such association was proposed (Fucci et al, 2020;Manfrini et al, 2020). TENT5 substrates do not harbor any detectable specific sequence motives and represent very abundant mRNAs, suggesting that the mechanism determining substrate specificity relies on localization rather than sequence recognition.…”
Section: Discussionsupporting
confidence: 68%
“…Accordingly, both TENT5A and TENT5C are clearly associated with membranes (Figure S6B; Bilska et al, 2020). TENT5C association with the ER was also recently confirmed by others, and the mechanism of such association was proposed (Fucci et al, 2020;Manfrini et al, 2020). TENT5 substrates do not harbor any detectable specific sequence motives and represent very abundant mRNAs, suggesting that the mechanism determining substrate specificity relies on localization rather than sequence recognition.…”
Section: Discussionsupporting
confidence: 68%
“…The polyadenylation activity of FAM46C is thought to be essential in this process by influencing the poly(A) tail length, hence the steady‐state levels of the mRNAs of Ig [ 27 , 28 ]. By forming complex with endoplasmic reticulum (ER)‐associated fibronectin type‐III domain‐containing protein A (FNDC3A) and FNDC3B, FAM46C remodels the trafficking and secretion of myeloma cells, which induces ER stress and impairs autophagy, eventually causing apoptosis [ 29 , 30 ]. Moreover, FAM46C is reported to physically interact with polo‐like kinase 4 (PLK4) and inhibits its kinase activity, thereby suppressing colorectal cancer in a PAP activity‐independent manner [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Family with sequence similarity 46, member C (FAM46C) is a member of the FAM46 family, it is located on chromosome 1p12 and seems to play a role in the regulation of translation by acting as an mRNA stabilizing factor. its abnormal deletions in tumor tissues were con rmed in multiple myeloma [20] and gastric cancer [21]. Zhang, et al reported that FAM46C was downregulated in hepatocellular carcinoma (HCC)and induced cell apoptosis through regulating Ras/MEK/ERK pathway [22].…”
Section: Discussionmentioning
confidence: 99%